2016
DOI: 10.1093/cercor/bhw033
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Movement Speed Over Direction in Neuronal Population Signals of Motor Cortex: Intracranial EEG Data and A Simple Explanatory Model

Abstract: How neuronal activity of motor cortex is related to movement is a central topic in motor neuroscience. Motor-cortical single neurons are more closely related to hand movement velocity than speed, that is, the magnitude of the (directional) velocity vector. Recently, there is also increasing interest in the representation of movement parameters in neuronal population activity, such as reflected in the intracranial EEG (iEEG). We show that in iEEG, contrasting to what has been previously found on the single neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 84 publications
(181 reference statements)
9
55
0
Order By: Relevance
“…In the current study, weights for the δ, θ and γ bands were higher than those of the other bands. This result is consistent with previous studies decoding for arm movement 7 , finger movement 14 , velocity 37 , and grasp type 38 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, weights for the δ, θ and γ bands were higher than those of the other bands. This result is consistent with previous studies decoding for arm movement 7 , finger movement 14 , velocity 37 , and grasp type 38 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported that weight values from δ and γ bands were effective and informative in trajectory decoding 36 37 38 . Crone et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, trial-wise variations of single neuron activations in M1 and PMd in the preparatory phase predicted some of the speed variability in the executed reach movement (Churchland, Afshar, & Shenoy, 2006a). In contrast to the monkey single-cell studies, Hammer et al (2016) recorded iEEG in and around human hand/arm motor cortex from large neuronal populations and found that single iEEG-electrode time series' correlated stronger with the undirected speed of movement than directed velocity. In contrast to the monkey single-cell studies, Hammer et al (2016) recorded iEEG in and around human hand/arm motor cortex from large neuronal populations and found that single iEEG-electrode time series' correlated stronger with the undirected speed of movement than directed velocity.…”
mentioning
confidence: 80%
“…We believe that these directions might not be sensitive enough to assess directional tuning with fMRI, as neurons with different preferred directions might fall within the same voxel and cancel each other out. According to Hammer et al (2016), directional tuning can be better characterized on the micro level, but its specificity degrades when the brain activity is recorded from larger neuronal populations (i.e., above 10,000 neurons) which is the case in the standard fMRI studies where each voxel represents the activation of approximately 500,000 neurons. Accordingly, two fMRI adaptation studies (Eisenberg et al, 2010;Fabbri et al, 2010) found orientation tuning in motor cortices when subjects repeatedly performed movements in the same direction.…”
Section: Directional Tuningmentioning
confidence: 99%
See 1 more Smart Citation